Non-destructive Detection of Insect Foreign Bodies in Finishing Tea Product Based on Terahertz Spectrum and Image - Sun, Xudong; Li, Jiajun; Shen, Yun; Li, Wenping (Frontiers in Nutrition, 2021)
Non-destructive detection (NDT) of low-density and organic foreign bodies is a main challenge for food safety control. Terahertz time-domain spectroscopy (THz-TDS) and time-resolved imaging technologies were applied to explore the feasibility of NDT method for the foreign bodies of insect imbedded in tea substrate. THz-TDS of tea substrate and foreign bodies of insect demonstrated significant differences in terms of time domain and frequency signals in the range of 0.3-1.0 THz. These signals were corrected by the use of adaptive iteratively reweighted penalized least squares (AirPLS), asymmetric least squares (AsLS), and baseline estimation and de-noising using sparsity (BEADS) for reducing baseline drift and enhancing effective spectral information. The k-nearest neighbor (KNN) and partial least squares discrimination analysis (PLS-DA) models showed the best performance after AirPLS correction with the prediction accuracy of 98 % and 100 %, respectively. Simultaneously, the THz time-resolved imaging provided a visual NDT method for tea substrate mixed with insect foreign bodies, because the locations and outlines of insect bodies could be clearly presented via the THz image. These results suggested that NDT of insects imbedded in tea substrate achieved by means of THz-TDS and time-resolved imaging, which were complementary with X-ray foreign body detection technology.